The Concept of Design Change Mechanism In Design and Build Contracts To Realize Legal Certainty - Laia, Alesman; Ismail, Ismail; Hartana, Hartana (Devotion : Journal of Research and Community Service, 2025)
The Design and Build (D&B) model is recognized for its potential to enhance efficiency by integrating planning and execution within a single contract. However, its implementation in Indonesia is hampered by the absence of a clear legal framework for managing design changes, leading to legal uncertainty and frequent disputes in strategic projects. This research aims to develop a clear and structured legal concept for a design change mechanism within Indonesian D&B contracts, grounded in the principles of legal certainty and fair risk allocation. The study employs a normative-juridical approach, analyzing Indonesian regulations (Law No. 2/2017, Presidential Regulation No. 16/2018) and comparing them with established international standards such as FIDIC and NEC4. The findings reveal that while Indonesian regulations generally permit contract modifications, they lack detailed procedures specifically for design changes in the D&B scheme. This regulatory gap results in ad hoc negotiations, imbalanced risk sharing, and weak documentation, weakening contractors' legal position. In contrast, international contracts provide structured procedures involving formal notification, impact assessment, and written instructions to ensure transparency. Based on these findings, the study concludes that the formulation of a standardized, procedural mechanism—covering application, evaluation, approval, adjustment, and documentation stages—is essential to ensure legal certainty. The research implies the need for amendments to national regulations or the development of ministerial guidelines that incorporate these principles, which would provide better legal protection, reduce project delays, and foster more equitable and efficient D&B project implementation in Indonesia